ICAM-1: Isoforms and Phenotypes - Ramos, Theresa N. (2014)
Intercellular adhesion molecule-1 (ICAM-1) plays an important role in leukocyte trafficking, immunological synapse formation and, numerous cellular immune responses. Although considered a single glycoprotein, there are multiple membrane bound and soluble ICAM-1 isoforms which arise from alternative splicing and proteolytic cleavage during inflammatory responses. The function and expression of these isoforms on various cell types is poorly understood. In the generation of ICAM-1-deficient mice, two isoform-deficient ICAM-1 mutants were inadvertently produced due to alternative splicing. These mice along with true ICAM-1-deficient mice and newly generated ICAM-1 transgenic mice have provided the opportunity to begin examining the role of ICAM-1 isoforms (singly or in combination) in various disease settings. In this review we highlight the sharply contrasting disease phenotypes using ICAM-1 isoform mutant mice. These studies demonstrate that ICAM-1 immunobiology is highly complex but that individual isoforms, aside from the full-length molecule, make significant contributions to disease development and pathogenesis.